Effect of Particle Size on Mechanical Properties of Al-RMp Metal Matrix Composites. (2017) - Rao, K.V. Sreenivas; Anil, K.C.; Akash; Girisha, K.G.
Abstract: Particle reinforced aluminum matrix composites (AMC) have invoked a potent interest in recent times for applications in aerospace industries. Al- MMCs have improved mechanical, tribological, strength to weight ratio when compare to monolithic metals and alloys. Red mud (RMp), a residue of a Bayer process was selected as reinforcement with three different grain sizes of 90, 120, 180 microns and wrought aluminum alloy 8011 as a matrix material. Normal stir casting route is adopted to cast the composites by varying the wt.% of the RMp from to 4% to 20% in increment of 4%. Prepared composites are then tested for mechanical properties as per the ASTM standards. From the obtained results it is observed that 24.45% increase in tensile strength in Al-14wt% RMp90 composition and good hardness and compressive strength in Al-20wt% RMp180 composition is obtained.